STUDI VARIASI PELARUT PADA REAKSI KONDENSASI ALDOL ANTARA FURFURAL DAN ASETON MENGGUNAKAN KATALIS MgO/γ-Al2O3 - Anjani, Ryzki Martha; Ulfa, Siti Mariyah; Tjahjanto, Rachmat Triandi (Jurnal Ilmu Kimia Universitas Brawijaya, 2014)
The aim of this research is to examine the effect of solvent’s polarity against the catalytic activity and selectivity of MgO/γ-Al2O3 catalysts for aldol condensation reaction between furfural and acetone. MgO/γ-Al2O3 catalyst made by wet impregnation method. The catalysts characterized by X-Ray Diffraction and Scanning Electron Microscopy-Electron Dispersive X-Ray Spectrometry. The reaction was conducted by reflux with the molar ratio 1:1 for furfural and acetone in N2 atmosphere (180 minutes). Water, ethanol:water 50%, and methanol used in this reaction as solvents. The result showed that MgO/γ-Al2O3have been higher activity for aldol reaction in water as a solvent and produced condensation product with the value of λmax was 300nm (measured by UV-Vis spectrophotometers).Prolonged the reaction time to 360 minutes increased the value of λmaxto be 312,5 nm. In ethanol:water and methanol solvent didn’t get the product of condensation. Key word: furfural, acetone, MgO/γ-Al2O3,aldol condensation, reflux.